Applications of Plant Protein in the Dairy Industry - Ge-Ge Hu (Foods, 2022)
In recent years, a variety of double protein dairy products have appeared on the market. It is a dairy product made by replacing parts of animal protein with plant protein and then using certain production methods. For some countries with limited milk resources, insufficient protein intake and low income, double protein dairy products have a bright future. More and more studies have found that double protein dairy products have combined effects which can alleviate the relatively poor functional properties of plant protein, including solubility, foaming, emulsifying and gelling. In addition, the taste of plant protein has been improved. This review focuses on the current state of research on double protein dairy products. It covers some salient features in the science and technology of plant proteins and suggests strategies for improving their use in various food applications. At the same time, it is expected that the fermentation methods used for those traditional dairy products as well as other processing technologies could be applied to produce novelty foods based on plant proteins.